The Application Degree of the Standards of U.S. National Council of Accreditation for teachers (NCATE) in the Faculty of Education at Taif University. - Abu Ola, Layla Abu Ola (Jordan Journal of Educational Sciences, 2016)
The current study aimed to identify the degree of practicing the NCATE Standards at the Faculty of Education at Al-Taif University. To achieve the objectives of the study a questionnaire was developed which included (48) items distributed into the six NCATE Standards: Program Offered", "Evaluation and Assessment", "Deanship and Resources", "Experiences", "Professional Development of faculty members" and the "Availability". After confirming validity and reliability, the researchers distributed the questionnaire on a sample of (155) faculty members in the Faculty of Education at Taif University out of the population (175). The study found that the degree of identify degree of practicing the NCATE standards at the Faculty of Education at Al-Taif University was medium. And that the degree of implementation of NCATE standards do not differ according to gender, academic rank, experience and all standards except the standard of "development of faculty members" it was in favor of males